2019
DOI: 10.2478/hukin-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Successful and Unsuccessful Snatch Lifts in Elite Female Weightlifters

Abstract: The aim of this study was to identify biomechanical factors affecting successful and unsuccessful snatch attempts in elite female weightlifters during the 2013 World Weightlifting Championships. Fourteen female competitors took part in this study. Their successful and unsuccessful snatch lifts with the same load were recorded with 2 camcorders (50 Hz), and selected points were digitized manually on to the body and the barbell using the Ariel Performance Analysis System. The kinetic and kinematic barbell moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In addition, it can be seen from the comparison curve of the center of gravity speed and displacement that martial arts routine athletes change evenly in the center of gravity speed during the entire movement process, which lays the foundation for their stable jumping support [ 10 ]. Through a series of data analysis, Mastalerz et al [ 11 ] concluded that, in the practice of martial arts jumping movements based on muscle strength, attention should be paid to strengthening the coordinated development of upper and lower limb muscle strength and the flexibility of the legs [ 11 ]. In the study by Tagaev et al [ 12 ], the kinematics comparative analysis of the sidekicks and the upright jumps of the martial arts routine athlete and Zhang Yanan, the two champions, was found in the comparison.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, it can be seen from the comparison curve of the center of gravity speed and displacement that martial arts routine athletes change evenly in the center of gravity speed during the entire movement process, which lays the foundation for their stable jumping support [ 10 ]. Through a series of data analysis, Mastalerz et al [ 11 ] concluded that, in the practice of martial arts jumping movements based on muscle strength, attention should be paid to strengthening the coordinated development of upper and lower limb muscle strength and the flexibility of the legs [ 11 ]. In the study by Tagaev et al [ 12 ], the kinematics comparative analysis of the sidekicks and the upright jumps of the martial arts routine athlete and Zhang Yanan, the two champions, was found in the comparison.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that higher skilled lifters have a faster movement under the barbell as displayed by an increase in their CoG velocity (8). This is also highlighted when comparing successful and unsuccessful snatches and maximal versus submaximal loads, where successful and maximal loads show an increase in velocity of CoG between the end of the second pull and peak bar height (30,48). Given the speed of the descent, it becomes difficult to identify stable components that are able to be seen through live observational analysis; however, it can be postulated that flexion of the knees should have begun in preparation for the catch when the barbell is at its peak height and the athlete should be descending into the receive position.…”
Section: Introductionmentioning
confidence: 93%
“…The first pull is recognized from the moment the plates are lifted from the floor to the point in which the knees are at their first maximum extension (7,15). This initial pull is believed to be critical in the performance of elite-level weightlifters, who have displayed greater relative maximal force capability than district-level lifters during the first pull (33). In addition, the first pull is integral to the efficiency of the entire lift facilitating a more efficient transition phase and, subsequently, a greater application of vertical ground reaction forces in the second pull (15).…”
Section: Introductionmentioning
confidence: 99%
“…No study has examined the relationship between peak force during the transition phase in weightlifting performance. The transition phase exhibits unique kinetic and kinematic characteristics, which requires a high level of technical ability (7,14,18,33,36). Considering the limited number of studies that have compared the different pulling positions on weightlifting performance, it was the purpose of this investigation to examine the association of force output and RFD in the 3 pulling phases to weightlifting performance in competitive Israeli weightlifters.…”
Section: Introductionmentioning
confidence: 99%